SUSTAINABILITY CORPORATE SOCIAL RESPONSIBILITY REVIEWED FROM COMPLIANCE THEORY - Winda Noviana; Aminah (ZILLZELL MEDIA PRIMA, 2025)
The rate of work accidents in Indonesia is still relatively high, with the number continuing to increase every year. The research aims to minimize the rate of work accidents in property and real estate sector companies listed on the Indonesia Stock Exchange during the 2021-2023 period. The study uses a quantitative method using a multiple linear regression approach to analyze the relationship between Corporate Social Responsibility (CSR) and compliance with compliance theory in Indonesia. The results of the study show that there is no significant influence between Company Growth on Compliance Theory. On the other hand, personal protective equipment has a significant effect on the theory of compliance. The discovery provides a view to the company's management to understand and emphasize the importance of using Personal Protective Equipment to maintain occupational safety and security.